Categorical perception in absolute pitch - RAKOWSKI, A. (Archives of Acoustics, 1993)
Three music students, possessing of absolute pitch, participated in an experiment of categorical identification of two adjacent musical pitch categories A#_4 and B_4. Next, they also participated in the experiment in which their ability to differenciate between two tone pulses separated by frequency level distance of 25 cents was tested. When ABX procedure was used with the tone-pulse length reduced to 20msec and the interstimulus interval extended to 10sec, the between-category discrimination in two sucjects markedly exceeded the within-category discrimination, which signalled the existence of categorical perception.